Purchase Intention on Instagram: The Roles of Digital Pricing Strategy, Social Media Engagement, and Perceived Value - Syahdan Muhada Assyaf; Ahmad Risman; Rita Zunarti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The widespread growth of social media has fundamentally reshaped how consumers make purchasing decisions and opened new avenues for businesses to shape buying behavior through digitally-driven marketing approaches. This study investigates how Digital Pricing Strategy, Social Media Engagement, and Perceived Value affect Purchase Intention among Health Administration students who use Instagram as a marketing platform. An explanatory quantitative approach was adopted using survey-based data collection. Structured questionnaires were distributed to 137 students selected through purposive sampling. The data were subsequently analyzed using PLS-SEM with the aid of SmartPLS 4 software. Findings reveal that Digital Pricing Strategy positively and significantly predicts Purchase Intention (β = 0.287, p < 0.001). Social Media Engagement emerged as the strongest predictor among the variables examined (β = 0.409, p < 0.001). Perceived Value, however, failed to reach statistical significance (β = 0.194, p = 0.058), suggesting that students' intention to buy on Instagram tends to be shaped more by social interaction dynamics, engagement features, and exposure to promotions than by rational assessments of product worth. The structural model accounted for 27.4% of the variance in Purchase Intention (R² = 0.274), indicating that the variables under study contribute meaningfully, though a considerable portion of unexplained variance points to the influence of factors beyond the scope of this model. These results underline the strategic value of fostering interactive engagement and implementing well-designed digital pricing approaches to drive purchase intention on social media. This study enriches the existing body of knowledge on digital marketing and consumer behavior while offering actionable guidance for businesses aiming to strengthen their Instagram marketing performance through deeper consumer engagement and more competitive pricing mechanisms.